College radio as a mechanism for participatory learning: Exploring the scope for online radio based learning among undergraduates - Bahaeldin Ibrahim; Naveen Mishra (Laureate Education Inc, 2016)
This paper explores the prospects of online college radio at Sur College of Applied Sciences, its need among students and the possible scope of its contributions to student learning, engagement and community service. It explores the method of developing a holistic mechanism to capture the possibilities of maximizing learning experience by employing college radio as an educational tool to understand the micro-dynamics and localized necessities that deem it necessary or unnecessary. Through this, it attempts to locate an appropriate mechanism, and targeted use of the college radio in contributing to the learning outcomes and educational experience of the students. The study finds considerable scope for radio based learning at Sur College of Applied Sciences across a range of uses and gratification indicators consistent with the primary objectives of the college. The study discusses the theoretical and practical implications of the findings, and the pedagogical significance of the college radio as an alternative.